Non-Compliance with COVID-19 Screening in Pakistan: A Cross-Sectional Survey - Furqan Ali Taj ,Muhammad Raheel Raza ,Saima Naz ,Muhammad Umar ,Aqsa Hameed (Journal of Rawalpindi Medical College, 2020)
Objectives: To quantify the non-complaint portion of the general public – not wanting to be screened for COVID-19 and find the reason for this non-compliance, in the general public of Rawalpindi Pakistan. Study Design: Cross-sectional survey. Place and Duration of Study: General public of Rawalpindi, Pakistan. From June 19, 2020, to June 21, 2020. Methodology: A questionnaire was constructed based on a local study, it was injected to the accessible online population through Google Forms. Surveyors collected data from the illiterate population on printed proforma. A sample of 1108 was collected. IBM® SPSS® was used for data analysis. For categorical data, frequencies and percentages were calculated. A Chi-square test was applied for statistical significance. Results: 45.3% of participants were females, 54.7% were males. 37.9% of participants were married and 62.1% were unmarried. 3.8% were illiterate, 40.4% were matriculated and 47.1% had education higher than intermediate. 38.3% was non-compliant population – didn’t want to get screened for COVID-19. 30.7% were non-compliant because of ‘fear of isolation/ quarantine with other COVID-19 patients, leading to worsening of disease’ followed by 26.9% who ‘don’t trust the reliability of the test’. Gender and Education level variables were statistically significant in determining non-compliance. Marital status was found non-significant. Conclusion: A significant portion of the population i.e. 38.3% showed non-compliance with COVID-19 screening, which was statistically associated with gender and education level.